Analysis Of Personality Conflicts Of The Characters In The Novel Az-Zayni Barakat By Jamal Al-Ghithanii (A Study Of Sigmund Freud's Literary Psychoanalysis) - Fauziah, Isma fauziah; Nurul Khotimah (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2024)
Personality Conflict using a literary psychology approach is a way to study the behavior of characters in a literary work. with psychological science, readers will explore the mental state of the characters in the literary work. this novel tells the story of Zayni Barakat, a prominent Egyptian muhtasib who also served as governor of Cairo at the end of the Mamluk dinasty. in the Mamluk era, a muhtasib was not only authorized to control the market situation, but also to monitor the behavior and morals of the people. and as Governor, in the midst of a chaotic political and security situation, he controlled the corrupt city through a network of spies and whistleblowers. Zayni Barakat was a pious and praiseworthy leader, honest and just, wise and with integrity, strong and decisive, disciplined and effective. He was much loved by his people. his partiality to the people is evident from his indiscriminate attitude towards the rich and the poor as well..............